Sie sind auf Seite 1von 2

3.5.36. If x 2 + xy + y 3 = 1, find the value of y at the point where x = 1.

Solution.

Factoring,

x 2 + xy + y 3 = 1

=2x + (xy) + 3y 2 y = 0 =2x + xy + y + 3y 2 y = 0.

 

y (x + 3y 2 )

=

(2x + y).

(1)

Differentiating again, we obtain:

 
 

y (x + 3y 2 ) + y (1 + 6yy ) =

(2 + y )

 

or

y (x + 3y 2 ) = y (1 + 6yy ) (2 + y ) = y 6y(y ) 2 2 y

 

or

 

y (x + 3y 2 )

=

y (2

+ 6yy ) 2.

(2)

Differentiating again, we obtain:

 
 

y (x + 3y 2 ) + y (1 + 6yy ) = y (2 + 6yy ) y (6yy )

 

or

y (x + 3y 2 ) +

y (1 + 6yy ) = y (2 + 6yy ) y (6y y + 6yy )

 

or further,

y (x + 3y 2 ) + y (1 + 6yy )

=

y (2 + 6yy ) 6((y ) 3 +

yy y ).

(3)

Now, when x

=

1, we obtain from x 2 + xy + y 3

= 1 that 1 + y + y 3

= 1, hence

y(y 2 + 1) = 0 =y = 0. Thus, from (3)

or

y (x + 3y 2 ) + y (1 + 6yy ) =

y (2 + 6yy )

6((y ) 3 + yy y )

becomes

y (1 + 3(0) 2 ) + y (1 + 6(0)y ) = y (2

+ 6(0)y ) 6((y ) 3 + (0)y y )

y + y = 2y 6((y ) 3 ) =

y = 3y 6(y ) 3 .

(4)

If x = 1 and y = 0, we obtain from (1) y (x + 3y 2 ) = (2x + y) that y (1 + 3(0) 2 ) = (2(1) + 0), hence y = 2. Thus, (4) becomes:

or

y

= 3y 6(y ) 3 = 3y 6(2) 3

y

=

3y + 48.

(5)

Finally, if x = 1, y = 0 and y = 2, we obtain from (2),

y (x + 3y 2 ) = y (2 + 6yy ) 2

that

y (1 + 3(0) 2 ) = (2)(2 + 6(0)(2)) 2,

or

Hence, from (5)

y = 2.

y = 3y + 48 = 3(2) + 48 = 42.